1987
DOI: 10.2307/2531952
|View full text |Cite
|
Sign up to set email alerts
|

A Dose-Response Model Incorporating Nonlinear Kinetics

Abstract: This paper introduces a dose-response model for toxic quantal response data based on hit theory applied to the dose unit as transformed by a nonlinear kinetic equation. When spontaneous background response is included in the model, the resulting dose-response model has four parameters. The maximum likelihood estimators and their large-sample properties are given. Likelihood ratio tests of interest are developed, including one for whether the model is one-hit in the transformed dose and one to check whether non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…, where is a constant, (2) and b -d is the natural background difference of cell proliferation rate and cell differentiation rate ofinitiated cells.…”
Section: Effects Of Metabolism Of Carcinogens That Are Promotersmentioning
confidence: 99%
See 1 more Smart Citation
“…, where is a constant, (2) and b -d is the natural background difference of cell proliferation rate and cell differentiation rate ofinitiated cells.…”
Section: Effects Of Metabolism Of Carcinogens That Are Promotersmentioning
confidence: 99%
“…For example, Hoel, Kaplan, and Anderson (1) have shown that it is not the exposed dose but the DNA adduct of agents that gives a linear dose-response curve for small doses. By using Michaelis-Menten kinetics, Van Ryzin and Rai (2) To provide a mathematical description of the carcinogenic process which can be used to interpret the results of experimental animal and human epidemiologic studies, Moolgavkar and Venzon (5) and Moolgavkar and Knudson (6) proposed a two-stage model of carcinogenesis. They modeled only two stages because no more than two distinct stages have been experimentally demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Modelling clustered data with informative cluster size is an active area of statistical research. Ryzin and Rai () first proposed to adjust for the cluster size directly as a covariate in the regression model and directly interpreted the cluster‐size‐adjusted regression model. Hoffman et al .…”
Section: Introductionmentioning
confidence: 99%
“…The mathematical model chosen was first used by Leonor Michaelis and Maud Menten in the early 20th century for a different purpose: to calculate the rate of enzyme-mediated reactions. The Michaelis-Menten kinetic model is usually invoked to explain uptake and elimination processes in toxicology (Newman 1998), but Van Ryzin andRai (1987) used it for describing the dose-response resulting from toxic effects in organisms. Apart from one isolated mention in the literature (Meister and Van den Brink 2000), to our knowledge this mathematical model has not been used to describe the time response of toxicants nor the kinetics of inhibition.…”
Section: Introductionmentioning
confidence: 99%